Kemajuan Teknologi dan Siasat untuk Berkembang - Ign Hening Swasono (Ars: Jurnal Seni Rupa dan Desain, 2011)
Technology Advance and Its Development Strategy.Art education organized by the Faculty of Visual Artof ISI Yogyakarta is related to the dynamic of the artdevelopment in the visual art practitioners’ networkingin both national and global level. The students enrichtheir knowledge and experience from inside as well asoutside the campus by employing various strategies.Within this process, at many times the effort in achievingan artistic convention crashes with the artistic creativitythat develops along with the world improvement. Marketundeniably has to be considered in assisting the studentsto be ‘mature’ artists. It is also a must that art interactswith other fields of science. Technology will hold animportant position as new learning resources in theeducation of art.